Determining physical and operational factors influencing pipeline leakage location pattern in water distribution networks using spatial poisson point process - Nugroho, W; Iriawan, N; Utomo, C (IOP conference series. Materials Science and Engineering, 2021)
There are four pillars in leakage management strategy for water distribution networks, consist of pressure management, speed of repairs, active leakage control, and asset management. Leakage can be managed by applying the right combination of those factors in the right leakage management strategy. This study conducted in Malang City, East Java, Indonesia. The factors that influence physical water loss in the water distribution system are analyzed by focusing on the physical and operational parameters. The data in this study consist of spatial data and quantitative data. Poisson distribution in the spatial point process is used as the leakage point distribution approximation. From the analysis, it is found that the distribution pattern of pipeline leakage location is categorized as inhomogeneous poisson process, with two types of intensity area. Based on the results of parameter estimation, it is found that the high-intensity area is affected by time of repairs, pipe diameter, pipe length ratio, water supply ratio, and pipe deterioration ratio but not affected by the hydraulic energy demand. While the low-intensity area is influenced by pipe diameter, pipe length ratio, water supply ratio, pipe deterioration ratio, and the hydraulic energy demand but not affected by the time of repairs.